ANALISIS TERHADAP PENCEGAHAN TINDAK PIDANA PENCUCIAN UANG OLEH BANK BNI DI TINJAU DARI UNDANG UNDANG NOMOR 8 TAHUN 2010 TENTANG TPPU - Nugroho, Nur (JURNAL MERCATORIA, 2016)
Formally, the prevention and eradication of criminal acts of money laundering in Indonesia began on 17 April 2002, ie when the enactment of Law No. 15 of 2002 on Money Laundering. Before the enactment of this Act phases of prevention of money laundering have been done but its scope is limited to banking. This can be demonstrated through a set of regulations issued by the banking authority, better known as Bank Indonesia Regulation concerning Know Your Customer. Urgency of this arrangement, of course based on solid arguments, especially regarding the impact of the money laundering activity in the economy and to meet the principles of effective bank supervision. Money laundering can undermine the national economy as it is very closely linked to the belief that one or another country against the policy of the State. Usually money laundering illicit money was made by mixing with legitimate money so that a legitimate business will not compete with companies who are honest, undermining the integrity of the financial markets due to the financial institutions (financial institutions) even rely on the proceeds of crime can face the danger of liquidity; resulting in a loss of government control of the economy of a country whose policies result in lack of confidence in other countries against its policies. This research was conducted in Bank BNI Cabang USU. In conducting the study, researchers conducted a study of documents about matters relating to the Prevention of Money Laundering. Fields that deal with money laundering in Bank BNI Cabang USU is the Compliance Division, in line with the needs after the end of 2015, the field of prevention is replaced by the Internal Controls under direct by branch managers. In carrying out its supervisory duties USU Bank BNI has implemented Law No. 8 of 20110 on AML with Bank Indonesia Regulation No. 11/28 / PBI / by applying the principle to know the Customer and step in stages in accordance with Circular No. 11/31 / DPNP Year 2009 Standard Guidelines for the Implementation of Anti-Money Laundering and Combating the Financing of Terrorism for Banks